Effect of Macroeconomic Variables on the Financial Performance of Deposit Money Banks in Nigeria - Simon Martha Ojoma; Oyedele Oloruntoba (Research Parks Publishers, 2022)
The study investigated the effect of macro-economic variables on the financial performance of Deposit Money Banks (DMBs) in Nigeria. The specific objectives of the study are; to examine the effects of interest rate on the financial performance of deposit money banks, to evaluate the effects of inflation on the financial performance of deposit money banks and to ascertain the effects of exchange rate on the financial performance of deposit money banks. The study utilised ex-post facto research design in its time series using multiple linear regression analysis. The data sources for the study were from the annual financial reports of the selected banks in Nigeria, international monetary fund and World Bank from 2005 to 2019. The major findings of the study showed that exchange rate and interest rate were statistically significant to financial performance of deposit money banks, while inflation rate is statistically insignificant to the financial performance of deposit money banks. The study adopted Return on Equity (ROE) as proxy for financial performance while exchange rate, inflation rate and interest rate were macro-economic indicators for financial performance of deposit money banks. The study concluded that a significant relationship exists between macro-economic variables and banks’ financial performance. The study therefore recommended that, banks should always take cognizance of macro-economic factor fluctuations; as its instability has the tendency to affect the financial performance of banks which consequently affects Return on Equity (ROE).